The genus Asianthrips, an Oriental fungus-feeding phlaeothripine (Thysanoptera, Phlaeothripidae) - Okajima, Shuji; Masumoto, Masami (Zootaxa, 2022)
The previously monobasic phlaeothripine genus Asianthrips is rediagnosed and revised with the following 17 new species: A. balianus sp. n., A. bamboosielloides sp. n., A. bicolor sp. n., A. borneoensis sp. n., A. dasycornis sp. n., A. dentipes sp. n., A. longior sp. n., A. magnus sp. n., A. malayanus sp. n., A. nobilis sp. n., A. pallens sp. n., A. parvinotus sp. n., A. setifer sp. n., A. sufflavus sp. n., A. sulawesiensis sp. n., A. taiwanus sp. n., A. vietnamensis sp. n. These species, all presumed to be fungus-feeding, are from seven different countries in Southeast Asia. An illustrated key is provided to 18 species in the genus.